STRATEGIC ANALYSIS OF COMPANY A IN THE INDONESIAN FOOD AND BEVERAGE INDUSTRY - Wahyun Islami; Aulia Moh Amidhan A; Tiara Puspa (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
Intensifying competition within Indonesia's food and beverage sector encourages firms to regularly reassess their strategic positions and develop initiatives that support long-term competitiveness and business sustainability. and formulate effective business development strategies. This study aims to analyze Company A’s internal and external environments and identify the most appropriate strategic alternatives to enhance its competitiveness and sustainable growth. A descriptive qualitative approach was employed using data collected through interviews, observations, documentation, and literature reviews. The analysis utilized the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Competitive Profile Matrix (CPM), SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM). The novelty of this study lies in the integration of IFE, EFE, CPM, SWOT, and QSPM analyses to comprehensively evaluate Company A’s strategic position within the food and beverage industry. The findings indicate that the company has a relatively strong internal position with an IFE score of 2.77 and is capable of responding effectively to external opportunities and threats, as reflected by an EFE score of 2.82. The CPM analysis revealed that although Company A remains competitive, it still lags behind major competitors in terms of brand image, distribution coverage, innovation, and financial capability. The SWOT analysis suggests growth-oriented strategies, while the QSPM identifies strengthening digital marketing, expanding distribution networks, and developing innovative products as the most attractive strategic priorities. The study concludes that Company A possesses strong growth potential and can improve its competitive advantage by implementing the recommended strategy. Future studies should incorporate financial performance indicators and broader industry comparisons to enhance strategic decision-making.